The Calligraphic Subject: The Body and Social Power in Malaysian "Abstract Expressionism" - Izmer Ahmad; Elham Shafaei Darestani (Wacana Seni Journal of Arts Discourse, 2017)
This article investigates the discourses surrounding "abstract expressionism" in modern Malaysian art. While stressing the local context and imageries in the readings of this particular episode in modern Malaysian art, we do not assume Malaysian "abstract expressionism" as existing independently from its western counterpart. Rather, we see the New York and Malaysian painters as co-extensive and that the latter has chosen to pursue an aspect of the former that has always already been in effect in New York since its inception in the 1940s–50s but had mutated differently in Malaysia under distinct historical and cultural trajectories. These, we argue, can be better understood once we attend closely to the stylistic feature, or more accurately, the visual vocabularies adopted by these artists which privileges the gesture of the painter. By doing so we may link "abstract expressionism" in Malaysia to the ideology of the body that is grounded in a nationalistic imaging.